Canadian stroke best practice recommendations: Secondary prevention of stroke, sixth edition practice guidelines, update 2017. Issue 4 (June 2018) - Wein, Theodore; Lindsay, M Patrice; Côté, Robert; Foley, Norine; Berlingieri, Joseph; Bhogal, Sanjit; Bourgoin, Aline; Buck, Brian H; Cox, Jafna; Davidson, Dion; Dowlatshahi, Dar; Douketis, Jim; et al.
The 2017 update of The Canadian Stroke Best Practice Recommendations for the Secondary Prevention of Stroke is a collection of current evidence-based recommendations intended for use by clinicians across a wide range of settings. The goal is to provide guidance for the prevention of ischemic stroke recurrence through the identification and management of modifiable vascular risk factors. Recommendations include those related to diagnostic testing, diet and lifestyle, smoking, hypertension, hyperlipidemia, diabetes, antiplatelet and anticoagulant therapies, carotid artery disease, atrial fibrillation, and other cardiac conditions. Notable changes in this sixth edition include the development of core elements for delivering secondary stroke prevention services, the addition of a section on cervical artery dissection, new recommendations regarding the management of patent foramen ovale, and the removal of the recommendations on management of sleep apnea. The Canadian Stroke Best Practice Recommendations include a range of supporting materials such as implementation resources to facilitate the adoption of evidence to practice, and related performance measures to enable monitoring of uptake and effectiveness of the recommendations. The guidelines further emphasize the need for a systems approach to stroke care, involving an interprofessional team, with access to specialists regardless of patient location, and the need to overcome geographic barriers to ensure equity in access within a universal health care system.